2014
DOI: 10.1186/2050-7445-2-3
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive multiresidue screening methods for the determination of pesticides in heritage collections

Abstract: Background: This paper describes the development of a novel non-invasive sampling and analysis method that can be used to assess the presence of volatile pesticides on objects held in heritage collections. Vapour phase sampling was conducted using sampling tubes loaded with Tenax-TA™ and trapped analytes were determined using thermal desorption-gas chromatography-mass spectrometry (TD-GC-MS). The results of this study are presented in a simple 'decision tree' diagram to provide the heritage sector with the bes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…186 Meanwhile, Gillingham rioters were said to have 'bound themselves by oaths to be true one to the other', pledging to act as a united group. 187 News and solidarity also spread beyond the forests' immediate vicinity. Requested to lend assistance in suppressing the riots, Henry Barrett, an innkeeper the town of Devizes twenty miles north of Braydon, 'in a contemptuous manner refused to goe' with 'jeering and unbeseeming speeches', reportedly inciting others by 'his ill example'.…”
Section: IImentioning
confidence: 99%
See 2 more Smart Citations
“…186 Meanwhile, Gillingham rioters were said to have 'bound themselves by oaths to be true one to the other', pledging to act as a united group. 187 News and solidarity also spread beyond the forests' immediate vicinity. Requested to lend assistance in suppressing the riots, Henry Barrett, an innkeeper the town of Devizes twenty miles north of Braydon, 'in a contemptuous manner refused to goe' with 'jeering and unbeseeming speeches', reportedly inciting others by 'his ill example'.…”
Section: IImentioning
confidence: 99%
“…Gillingham rioters were reported to 'throw down, and fill up the ditches and fences there about three miles in length', methodically sawing up and burying the rails and posts. 191 The role of physical boundaries in spatially and symbolically manifesting private property was reflected in complaints that Braydon commoners had destroyed enclosing hedges so that 'the farmers should never be able to improve or inclose' and 'all things is nowe in comon'. 192 Rioters also collectively expropriated forest resources, killing deer and cutting down trees in Gillingham and thereby openly claiming venison and vert which had hitherto been covertly poached and pilfered.…”
Section: IImentioning
confidence: 99%
See 1 more Smart Citation
“…Naphthalene is a common volatile pesticide residue found in museum collections [2,4,8,[14][15][16]. The choice of the compound for this study was arbitrary as it was the most common present in the chosen objects.…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al (2006) suggested the use of mesoporous silica as a collector of VOCs. Tenax TA and other commercial sorbents have also been reviewed for their proposed ability to collect VOCs (Harper 2000, Rushworth et al 2014. Idris et al (2010) proposed the use of Tenax TA as a VOC collector because it is less susceptible to changes in the RH compared with mesoporous silica.…”
Section: Evaluating Potential Risk To Organic Objectsmentioning
confidence: 99%